2010
DOI: 10.1038/gene.2010.42
|View full text |Cite
|
Sign up to set email alerts
|

Members 6B and 14 of the TNF receptor superfamily in multiple sclerosis predisposition

Abstract: TNFRSF6B and TNFRSF14 genes were recently associated with Crohn's disease and rheumatoid arthritis. TNFRSF14 is known as herpes virus entry mediator (HVEM), and herpes viruses have been involved in the aetiology of multiple sclerosis (MS). MS patients present human herpes virus 6 (HHV6) in active plaques and increased antibody responses to HHV6. We aimed to ascertain the role of these genes in MS susceptibility and to investigate the relationship of the gene encoding the widely expressed HVEM receptor with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 31 publications
(25 reference statements)
2
10
0
Order By: Relevance
“…Breast IDC is the most common breast cancer type in women. Previous research concerning DcR3 polymorphisms is scarce [ 19 , 20 ], especially with respect to cancer [ 21 ]. DcR3, as a member of the tumor necrosis factor superfamily of co-stimulatory molecules, promotes cellular invasion and migration in MCF7 breast cancer cells, and may be a negative regulator for aggressiveness during breast cancer development and progression [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Breast IDC is the most common breast cancer type in women. Previous research concerning DcR3 polymorphisms is scarce [ 19 , 20 ], especially with respect to cancer [ 21 ]. DcR3, as a member of the tumor necrosis factor superfamily of co-stimulatory molecules, promotes cellular invasion and migration in MCF7 breast cancer cells, and may be a negative regulator for aggressiveness during breast cancer development and progression [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, although an overwhelming majority of post-transplant reactivation occurs with HHV-6B [28, 29, 53], HHV-6A DNA and mRNA are found more frequently than HHV-6B in patients with neuroinflammatory diseases such as multiple sclerosis (MS) [9, 14, 48, 115] and rhomboencephalitis [37]. HHV-6A has been found predominantly in the CNS of a subset of patients with MS, and active HHV-6A infection has been detected in blood [8, 9, 11] and in CSF [110] of patients with relapsing/remitting MS [810, 14, 20, 110, 115, 131]. Marmosets inoculated with HHV-6A intravenously exhibited neurological symptoms, whereas those inoculated with HHV-6B were asymptomatic [75].…”
Section: Distinct Epidemiology and Disease Associationsmentioning
confidence: 99%
“…A study of the gene found that the rs6684865 variant predisposed to MS, with a greater effect in patients positive for herpesvirus. 22 This gene also shows an association with MS susceptibility, according to a study by the International Multiple Sclerosis Genetics Consortium. 8 The above-mentioned polymorphism should be studied in the future.…”
Section: Tnfrsf10dmentioning
confidence: 99%